Religious Affiliation Predicts Prejudice and Prosocial Behavior - Butcher, Cody; DeLaPena, Alex; Selvanathan, Hemapreya (My University, 2013)
The relationship between religion, prejudice and prosocial behavior is complex. Religion has long provided a tenet of goodness, contributing to the widely held belief that religious adherence is associated with lower prejudice and greater helping. However, evidence exists to the contrary (Pargament, 2002). This study sought to replicate and extend the findings of previous researchers by evaluating the relationships between religious affiliation and prejudice, and between religious affiliation and helping. Additionally, this study sought to compare levels of prejudice and helping between believers and nonbelievers.
Color poster with text and graphs.
Keywords: Religious affiliation; Bias; Volunteerism; Posters